Selected Papers on the History of Medicine and Healthcare (2014) - Pratt, William J. (Cambridge Scholars Publisher, 2019)
This volume continues the Proceedings of the Calgary History of Medicine Days series which publishes the work of young and emerging researchers in the field, hence providing a unique publishing format. The annual Calgary History of Medicine Days Conference, established in 1991, brings together undergraduate and early graduate students from across Canada, Latin America, the United States, the United Kingdom, and Europe to give paper and poster presentations on a wide variety of topics from the history of medicine and healthcare from a multiple perspectives. The History of Medicine Days offers a.